Pengendalian Persediaan Untuk Mengurangi Biaya Total Persediaan Dengan Pendekatan Metode Periodic Review (R,s,S) Power Approximation Pada Suku Cadang Consumable (Studi Kasus : Job Pertamina Talisman Jambi Merang) - Mahardika, Adhi Putra; Ardiansyah, Muhammad Nashir; Yunus, Efrata Denny S. (Jurnal Rekayasa Sistem Industri, 2015)
Spare parts is one of the production support components which plays an important role for the survivalof gas production in the gas processing facility owned by SKN JOB Pertamina Talisman Jambi Merang. Thehigh inventory level increased the high inventory cost for the industry which get the benefit from the efficiencyof processes and resources. This research involved consumable spare parts for Solar Turbine engine as muchas 25 SKUs with demand character patterned lumpy demand and Poisson distribution. The implementationof policies using Periodic Review (R, s, S) with Power Approximation approach in the inventory systemcapable to generate a lower total cost inventory by pressing the backorder volume, the booking volume and theinventory levels in a balanced manner. Calculation of Periodic Review (R, s, S) with Power Approximationapproach resulted inventory parameter which was able to press the total cost of inventory at 8.54% lower andincrease the service level by 1.11%.